An Analysis of the Application of the Theory of “Treatment of Future Diseases” in Different Cancers - Zhao, Zhilong; Hou, Junming (Journal of Contemporary Medical Practice, 2025)
Malignant tumours have become the primary disease that endangers the physical and mental health of the global population, causing a serious burden on the public health of each country, especially in China with such a large population base, which makes the reasonable prevention and treatment of tumours even more difficult, as this topic, through reading and analysing the theory of “treating the future illness”, we propose the application of the theory of “treating the future illness” in different malignant tumours, and elaborate on the application of the theory of “treating the future illness” in different cancers. By reading and analysing the related literature and the monograph of “Emperor’s Classic of Internal Medicine”, we proposed the application of the idea of “treating the future illness” in different malignant tumours, elaborated the origin of “treating the future illness” and the connection with oncology, and introduced four levels of treatment in different tumours, namely, preventing the disease before it starts, treating the disease before it begins, preventing the change of the disease before it begins and preventing the recurrence of the disease after it is healed, and introduced the four levels of treatment in different tumours. It also introduces the application of the four levels of treatment of the future disease in different tumours.